A systematic review and meta-analysis on antimicrobial resistance in marine bivalves - Albini, Elisa; Orso, Massimiliano; Cozzolino, Francesco; Sacchini, Luca; Leoni, Francesca; Magistrali, Chiara Francesca (Frontiers in Microbiology, 2022)
Bivalves are filter-feeding animals able to accumulate contaminants and microorganisms, either of marine or terrestrial origin. The aim of this study was to describe the prevalence of antimicrobial resistance (AMR) in bacterial isolates from bivalves using a systematic review of the literature. Comprehensive searches of MEDLINE, EMBASE and Web of Science were carried out, based upon a registered protocol (PROSPERO), and following the preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. The methodological quality of the included studies was assessed using a modified Hoy checklist. Meta-analyses of prevalence were carried out using random-effects models. In total, 103 articles were selected from 1,280 records and were included in the final analysis. The studies were from Asia (n = 54), Europe (n = 27), South and North America (n = 10 and n = 6, respectively), Africa (n = 2), Oceania (n = 1) and multicenter and intercontinental (n = 3). The meta-analysis of multiple antibiotic resistance (MAR) index revealed Aeromonas spp. as the genus with the highest prevalence of AMR (37%), followed by Vibrio spp. (34%), Salmonella spp. (18%) and Escherichia coli (15%). Resistance to third/fourth/fifth generation cephalosporins and fluoroquinolones, two highest priority, critically important antimicrobials (HPCIA), was recorded in approximately 10% of E. coli isolates. Resistance to carbapenems was very low (< 2%) in Salmonella spp. and in E. coli, but was found in 5% of Vibrio spp. and in more than a third of Aeromonas spp. isolates. In aquatic bacteria, resistance to carbapenems was higher in Asian than in European isolates. Our study shows the presence of ARB, including bacteria resistant to HPCIA, in marine bivalves, posing a risk for consumers.